Electrochemical Glycerol Valorization Using Tolerant Pt Embedded Bi Platform Electrocatalysts Derived From Photoactive Bismuth Oxyiodide Nanosheet Intermediates - Hak Hyeon Lee; Ji Hoon Choi; Dong Su Kim; Sungho Jeon; Eric A. Stach; Hyung Koun Cho (EcoMat)
ABSTRACT Pt‐based electrocatalysts for glycerol oxidation reaction (GOR) exhibit low durability due to the inactivation of Pt through rapid poisoning under oxidative conditions. Thus, bimetallic PtBi was strategically synthesized using BiOI as a photoactive intermediate for the uniform photoelectrodeposition of Pt. The nanostructured Pt–Bi was electrochemically reduced from a Pt/BiOI medium, and the GOR‐activated Pt–Bi electrocatalysts (G–Pt–Bi) were obtained via a subsequent electrochemical activation process. Here, abundant Bi sites in PtBi can prevent Pt poisoning and effectively provide adsorbed OH− for the GOR on Pt sites. Consequently, it allows the operation in low onset potential for GOR with a high mass activity of 13.35 A mgPt −1 at 0.85 VRHE in alkaline solution. The GOR products obtained using G–Pt–Bi were identified as glycolate and formate by 1H‐nuclear magnetic resonance without the interruption of the hydrogen evolution reaction, and it finally enables the operation of a membrane‐free two‐electrode system. In situ electrochemical impedance spectroscopy demonstrates that the G–Pt–Bi exhibit superior GOR kinetics and higher resistance to Pt inactivation compared with conventional Pt/C. This study suggests a novel design for a G–Pt–Bi architecture in developing durable and high‐mass‐activity Pt catalysts for the GOR.